“Anugrah atau Musibah”: Pinjaman Online di Kalangan Mahasiswa - Umboh, Lutfia (Universitas Muslim Maros, 2024)
The proliferation of online loan (pinjol) users among students is not something new, in fact many studies have examined the use of online loans, which focus more on the ease of accessing online loans. This article focuses on the reasons and impacts of using online loans among university students. Using qualitative approach, this study was carried out in Makassar City between September and December 2023. There were ten informants who participated in this study, consisting of seven women and three men, with an age range of 20 to 21 years. In this study, in-depth interviews and observation methods were used as data collection techniques. The results of this research show students have many needs, but at the same time have limited funds whike they depend on their parents. So they will look for various alternatives to have money and to meet their needs, one way is to borrow money. In this modern era, technology and financial sector are innovating to create new services, namely online loans. Online loans help the general public, including students, who need fast funds with easy requirements and quick process. The reasons why students use loans are divided into two, namely: to meet urgent needs (such as buying books, paying boarding houses, and paying off debts); and to meet their entertainment needs (such as online shopping and gambling capital). If online loans are used for urgent needs, then borrowing is a